2013
DOI: 10.4110/in.2013.13.4.148
|View full text |Cite
|
Sign up to set email alerts
|

The Soluble Form of the Cellular Prion Protein Enhances Phagocytic Activity and Cytokine Production by Human Monocytes Via Activation of ERK and NF-κB

Abstract: The PrPC is expressed in many types of immune cells including monocytes and macrophages, however, its function in immune regulation remains to be elucidated. In the present study, we examined a role for PrPC in regulation of monocyte function. Specifically, the effect of a soluble form of PrPC was studied in human monocytes. A recombinant fusion protein of soluble human PrPC fused with the Fc portion of human IgG1 (designated as soluble PrPC-Fc) bound to the cell surface of monocytes, induced differentiation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…A previous report showed that a PrP C -Fc fusion protein induced phosphorylation of ERK and PI3K in a macrophage-like cell line [10]. In addition, a recent study from our group showed that PrP C -Fc activates monocytes via the ERK-1/2 and NF-kB signaling pathways [11]. The discrepancies of signaling pathways involved in the immune cell activation by soluble PrP C -Fc protein may arise from differences in cell types, particularly the difference between monocyte/macrophage cells and NK cells.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A previous report showed that a PrP C -Fc fusion protein induced phosphorylation of ERK and PI3K in a macrophage-like cell line [10]. In addition, a recent study from our group showed that PrP C -Fc activates monocytes via the ERK-1/2 and NF-kB signaling pathways [11]. The discrepancies of signaling pathways involved in the immune cell activation by soluble PrP C -Fc protein may arise from differences in cell types, particularly the difference between monocyte/macrophage cells and NK cells.…”
Section: Discussionmentioning
confidence: 93%
“…A recombinant soluble human PrP C protein was generated and purified as previously described [11]. Briefly, a plasmid encoding PrP C -Fc, composed of amino acids 21e230 of human PrP C fused with the Fc portion of human IgG1 at the C-terminus, was expressed in HEK293E cells.…”
Section: Generation and Purification Of Recombinant Human Prp C -Fcmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Levels of prion protein expressed in mouse neutrophils have also been shown to be dependent on HPA axis activation during inflammation events. 173 Interestingly, no other bone marrow cell showed this response.…”
Section: Prp C Immune System and Phagocytosismentioning
confidence: 99%
“…PrP C appears to be neuroprotective against the build-up of α-synuclein, β-amyloid, and tau plaques, 245 possibly as a result of its influence on phagocytosis and neuroregulation. 11 PrP C has also recently been suggested as a therapeutic agent in the treatment of Alzheimer's disease. 246,247 The relationship between PrP C and Alzheimer's disease has been the subject of a number of recent reviews.…”
mentioning
confidence: 99%